2017
DOI: 10.1016/j.jmb.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The C-Box Region of MAF1 Regulates Transcriptional Activity and Protein Stability

Abstract: MAF1 is a conserved negative regulator of RNA polymerase (pol) III and intracellular lipid homeostasis across species. Here, we show that the MAF1 C-box region negatively regulates its activity. Mutations in Caenorhabditis elegans mafr-1 that truncate the C-box retain the ability to inhibit the transcription of RNA pol III targets, reduce lipid biogenesis, and lower reproductive output. In human cells, C-box deletion of MAF1 leads to increased MAF1 nuclear localization and enhanced repression of ACC1 and FASN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…Similarly, mafr-1 (KO) animals displayed increased intracellular lipid abundance relative to age-matched WT control animals ( Fig. 1E), as expected from previous studies (Khanna et al, 2014;Mierzejewska and Chreptowicz, 2016;Palian et al, 2014;Pradhan et al, 2017). Our previous investigations revealed that overexpression of mafr-1 can influence reproductive output (Khanna et al, 2014).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, mafr-1 (KO) animals displayed increased intracellular lipid abundance relative to age-matched WT control animals ( Fig. 1E), as expected from previous studies (Khanna et al, 2014;Mierzejewska and Chreptowicz, 2016;Palian et al, 2014;Pradhan et al, 2017). Our previous investigations revealed that overexpression of mafr-1 can influence reproductive output (Khanna et al, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Characterization of a mafr-1 null mutant Previous studies of mafr-1 in C. elegans have utilized RNAi-based approaches (Khanna et al, 2014) and a gain-of-function allele of mafr-1 (Pradhan et al, 2017) leaving the true loss-of-function phenotype unknown. To better examine the biological functions of MAFR-1, we assessed the impact of a true molecular null allele of mafr-1, hereafter referred to as mafr-1 (KO) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TOR inhibition and calorie restriction) lead to Maf1-dependent repression [11,14,43] while deletion of Maf1 in yeast reduces chronological lifespan [42,44]. The tm6082 allele removes the phylogenetically conserved box C region, including three of the four β-sheets that make up the central core of Maf1 along with additional sequences (a total of 79 amino acids) and introduces 37 different amino acids in their place [42,45,46]. Interestingly, rather than shortening lifespan, the tm6082 mutant extended lifespan under both normal and calorie-restricted conditions.…”
Section: Impact Of Maf1 On Cell Physiology In Metazoansmentioning
confidence: 99%
“…Lifespan extension in the tm6082 mutant was also suppressed by Maf1 overexpression demonstrating that the phenotype is due to a loss of Maf1 function. Curiously, other phenotypes identified using the tm6082 allele in a different study were interpreted as resulting from a gain of function [45]. It is not clear how to reconcile these observations as neither study examined the levels of Maf1 mRNA or protein in the tm6082 mutant.…”
Section: Impact Of Maf1 On Cell Physiology In Metazoansmentioning
confidence: 99%